(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Chemistry is important in the formation of not only theoretical knowledge, but also practical skills in the educational process. Teaching students through non-standard experiments in chemistry is effective in increasing their interest and developing scientific thinking. This article talks about the advantages, methods and role of using non-standard experiments in teaching chemistry.